The Meaning of al-Hurriyyah in QS. al-Baqarah [2]: 256 and QS. al-Kahfi [18]: 29: A Maqâṣid Approach of Ibn ‘Asyur - Ahmad Zainal Mustofa; Nurus Syarifah (Jurnal Ushuluddin, 2021)
Ibn ‘Asyur is a modern Muslim scholar, he is also a commentator and expert on jurisprudence. His well-known works of interpretation and fiqh suggestions are Tafsir al-Tahrir wa al-Tanwir and Maqâṣid al-Syari’ah al-Islamiyyah. Furthermore, this article explores the meaning of “alhurriyyah” in the context of the maqâṣid al-syari’ah from the perspective of Ibn ‘Asyur. The object in this discussion is his interpretation work entitled Tafsir al-Tahrir wa al-Tanwir, which focuses on analysis in QS. 2: 256 and QS. 18: 29. This research is motivated by the new maqâṣid al-syari’ah concept which was initiated by Ibn ‘Asyur since the vacuum of the maqâṣid concept which was previously brought by al-Syathibi. This concept of Ibn ‘Asyur is universally oriented. One of the terms in the maqâṣid al-syari’ah is “al-hurriyyah.” This research was conducted to answer questions about how the concept of maqâṣid al-syari’ah Ibn ‘Asyur is implemented in the QS. 2: 256 and QS. 18: 26. The method used in this research is descriptive analytical. After conducting theresearchit can be concluded that in the two letters that have been analyzed, the meaning of “al-hurriyyah” which is meant by Ibn ‘Asyur is a freedom to choose the religion that is believed and there is no compulsion in choosing it. Ibn ‘Asyur explained that a Muslim is allowed to help fellow humans in the social aspect and not in the aspect of religion, belief or creed